2007
DOI: 10.1152/ajpgi.00526.2006
|View full text |Cite
|
Sign up to set email alerts
|

Increased gastric expression of MMP-7 in hypergastrinemia and significance for epithelial-mesenchymal signaling

Abstract: Chronic hypergastrinemia is associated with enterochromaffin-like (ECL) cell hyperplasia, which may progress to gastric carcinoid tumors. The latter consists of epithelial cells and stroma, and both compartments usually regress after normalization of hypergastrinemia. We previously showed that matrix metalloproteinase (MMP)-7 in gastric epithelial cells was upregulated by Helicobacter pylori and described MMP-7-dependent reciprocal signaling between the epithelium and a key stromal cell type, the myofibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 36 publications
3
43
0
1
Order By: Relevance
“…Gastrin has been reported to have a growth factor-like effect on gastric cells, and we have previously reported that Reg I, amphiregulin, and some of MMP family members, such as MMP-7, -9, -10, and -13 were up-regulated in INS-GAS mice of FVB/N background. 23,26,27 In the current study, we confirmed up-regulation of these genes except MMP-7 and -10 as shown in Figure 6, A-C. Previously we have reported that H. felis or H. pylori infection of INS-GAS male mice in an FVB/N background rapidly leads to corpus gastric cancer at 7 to 8 MPI.…”
Section: Discussionsupporting
confidence: 87%
“…Gastrin has been reported to have a growth factor-like effect on gastric cells, and we have previously reported that Reg I, amphiregulin, and some of MMP family members, such as MMP-7, -9, -10, and -13 were up-regulated in INS-GAS mice of FVB/N background. 23,26,27 In the current study, we confirmed up-regulation of these genes except MMP-7 and -10 as shown in Figure 6, A-C. Previously we have reported that H. felis or H. pylori infection of INS-GAS male mice in an FVB/N background rapidly leads to corpus gastric cancer at 7 to 8 MPI.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, pertinent changes in epithelialmesenchymal signaling have been linked to increases in gastrin expression, another effect of PPI therapy [28]. Although we cannot definitively ascribe the leak we observed to the tight junction per se, the above actions could negatively impinge on barrier elements.…”
Section: Discussionmentioning
confidence: 79%
“…The different cell types in the microenvironment become stimulated by cancer cell-produced factors such as TGF-β, EGF, TGF-α, PDGFs, FGFs, IGFs, shh and MMPs [69,72,[75][76][77][78][79]. In turn, stromal cells respond by producing growth factors (e.g.…”
Section: Signals Stimulating Cancer Cell Growth Migration Invasion mentioning
confidence: 99%